Determining the effect of therapeutic play on fear, anxiety levels, and behavioural responses ın children receiving high-flow nasal cannula oxygen treatment: A randomized controlled study - Cetin, Kerime Deniz Kilic; Coskun Simsek, Didem (Elsevier Science Inc, 2025)
Purpose The aim of this study was to determine the effects of therapeutic play on the fear and anxiety levels and behaviours of children receiving high-flow nasal cannula oxygen therapy. Design and method This study was conducted as a pre-test - post-test randomized controlled study. The study was conducted in the Paediatric Intensive Care Unit of a state hospital located in a province of the Central Anatolia Region of Turkey between June and December 2024. The study was conducted with children aged between four to eight. Therapeutic play, involving amigurumi toys and illustrated colouring cards, was administered to children in the intervention group. Therapeutic session was started ten minutes before the high-flow nasal cannula oxygen treatment and continued throughout the procedure, lasting approximately 30 min in total. No intervention was provided to the children in the control group during the study. Data collection tools included the 'Child and Parent Information Form', 'Children's Fear Scale', 'Child Anxiety Scale-State' and 'Child Observation Form'. were analysed using frequencies, percentages, means, standard deviations, Chi-Square Test, Fisher's Exact Test, Independent Samples t-test, and the General Linear Model. Results In the experimental group, 55.3 % of the children were 4 years old and 23.4 % were 5 years old, while in the control group, 43.8 % of the children were 4 years old and 25 % were 5 years old. The difference in age distribution between the groups was found to be statistically non-significant (p = 0.647). It was found that the mean score of the Children's Fear Scale and Children's Anxiety Scale-State in the experimental group was lower than in the control group and the difference between them was statistically significant. The children in the experimental group showed less crying, removing the nasal cannula and restlessness during the high-flow nasal cannula oxygen treatment compared to the control group (p < 0.05). Conclusions Therapeutic play has been shown to have a positive effect on the behaviours of children receiving high-flow nasal cannula oxygen therapy by reducing their fear and anxiety levels. Practice implications Therapeutic play is safe and effective intervention that can be applied to children receiving high-flow nasal cannula oxygen therapy. Hospitals should ensure that materials for the use of therapeutic play are available, and paediatric nurses should use therapeutic play extensively to prepare children for medical procedures and during procedures. (c) 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Amigurumi toy; Anxiety; Behaviour; Fear; Therapeutic play